Palliative Lung Radiotherapy: Higher Dose Leads to Improved Survival?. Issue 10 (October 2020) - Lewis, T.S.; Kennedy, J.A.; Price, G.J.; Mee, T.; Woolf, D.K.; Bayman, N.A.; Chan, C.; Coote, J.H.; Faivre-Finn, C.; Harris, M.A.; Hudson, A.M.; Pemberton, L.S.; et al.
Abstract: Aims: Choosing the optimal palliative lung radiotherapy regimen is challenging. Guidance from The Royal College of Radiologists recommends treatment stratification based on performance status, but evidence suggests that higher radiotherapy doses may be associated with survival benefits. The aim of this study was to investigate the effects of fractionation regimen and additional factors on the survival of palliative lung cancer radiotherapy patients. Materials and methods: A retrospective univariable ( n  = 925) and multivariable ( n  = 422) survival analysis of the prognostic significance of baseline patient characteristics and treatment prescription was carried out on patients with non-small cell and small cell lung cancer treated with palliative lung radiotherapy. The covariates investigated included: gender, age, performance status, histology, comorbidities, stage, tumour location, tumour side, smoking status, pack year history, primary radiotherapy technique and fractionation scheme. The overall mortality rate at 30 and 90 days of treatment was calculated. Results: Univariable analysis revealed that performance status ( P  < 0.001), fractionation scheme ( P  < 0.001), comorbidities ( P  = 0.02), small cell histology ( P  = 0.02), 'lifelong never' smoking status ( P  = 0.01) and gender ( P  = 0.06) were associated with survival. Upon multivariable analysis, only better performance status ( P  = 0.01) and increased dose/fractionation regimens of up to 30 Gy/10 fractions ( P  < 0.001) were associated with increased survival. Eighty-five (9.2%) and 316 patients (34%) died within 30 and 90 days of treatment, respectively. Conclusion: In this retrospective single-centre analysis of palliative lung radiotherapy, increased total dose (up to and including 30 Gy/10 fractions) was associated with better survival regardless of performance status. Highlights: Larger doses of palliative lung radiotherapy are associated with increased survival. Performance status is independently linked to survival. Palliative lung radiotherapy dose is independently linked to survival.